2014
DOI: 10.1371/journal.pone.0103305
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Mir-21/PTEN Expression Modulates Gefitinib Resistance in Non-Small Cell Lung Cancer

Abstract: Resistance to TKI treatment is a major obstacle in effective treatment of NSCLC. Besides EGFR mutation status, the mechanisms involved are largely unknown. Some evidence supports a role for microRNA 21 in modulating drug sensitivity of chemotherapy but its role in NSCLC TKI resistance still remains unexplored. This study aimed to investigate whether NSCLC miR-21 mediated resistance to TKIs also results from Pten targeting. Here, we show miR-21 promotes cancer by negatively regulating Pten expression in human N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
92
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 59 publications
(66 reference statements)
7
92
1
Order By: Relevance
“…In addition to the well-known platinum-based chemotherapy for lung cancer, miR-21 has been shown to be involved in the resistance to the EGFR inhibitor. EGFR-tyrosine kinase inhibitor (TKI) has been regarded as an important treatment option for NSCLC and miR-21 overexpression was found to be associated with acquired resistance to EGFR-TKI (77,78). A pilot study using plasma miRNA profiles identified miR-21 to be involved in the primary resistance to EGFR-TKI in patients with advanced NSCLC with an activating EGFR mutation.…”
Section: Mir-21 and Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the well-known platinum-based chemotherapy for lung cancer, miR-21 has been shown to be involved in the resistance to the EGFR inhibitor. EGFR-tyrosine kinase inhibitor (TKI) has been regarded as an important treatment option for NSCLC and miR-21 overexpression was found to be associated with acquired resistance to EGFR-TKI (77,78). A pilot study using plasma miRNA profiles identified miR-21 to be involved in the primary resistance to EGFR-TKI in patients with advanced NSCLC with an activating EGFR mutation.…”
Section: Mir-21 and Solid Tumorsmentioning
confidence: 99%
“…The application of this non-invasive approach may be considered for monitoring responses of lung cancer patients to EGFR-TKI treatment (79). Furthermore, the implication of miR-21 in chemotherapy resistance has been investigated for a wide range of solid cancer types, including pancreatic and prostate cancer, hepatoma, ovarian cancer, glioma, and head and neck, stomach and bladder cancer (Table I) (68)(69)(70)(71)75,(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94). These results support the clinical application of miR-21 inhibition in cancer treatments in the future.…”
Section: Mir-21 and Solid Tumorsmentioning
confidence: 99%
“…Additionally, the inhibition of miR-21 induced apoptosis in the PC9R cell line and inhibited miR-21, while miR-21 antisense oligo nucleotide (ASO) suppressed tumor growth in nude mice treated with EGFR-TKI (18). Shen et al (33) revealed that high miR-21 expression indicated a poor TKI clinical response and a shorter overall survival rate. miR-21 expression was upregulated in PC-9 gefitinib resistant cells (PC-9/GR) compared with PC-9 cells and miR-21 knockdown markedly restored gefitinib sensitivity in PC-9/GR cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al (33) revealed that high miR-21 expression indicated a poor TKI clinical response and a shorter overall survival rate. miR-21 expression was upregulated in PC-9 gefitinib resistant cells (PC-9/GR) compared with PC-9 cells and miR-21 knockdown markedly restored gefitinib sensitivity in PC-9/GR cells (33). Similar to previous studies, the results of the present investigation revealed that miR-21 expression was elevated in gefitinib-resistant lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-21 has also been suggested to be regulated by reactive oxygen species-activated ERK/NF-B in arsenite-induced cell transformation [248]. Others have suggested that miR-21 is both a target and regulator of ERK/NF-B and JNK/c-jun axis [254]. My data show that LPS-induced ERK activation was diminished in miR-21-KO cells.…”
Section: Mir-21 and Activation Of Caspases In Macrophagementioning
confidence: 71%